2022
DOI: 10.1038/s41419-022-04971-x
|View full text |Cite
|
Sign up to set email alerts
|

STAT6 inhibits ferroptosis and alleviates acute lung injury via regulating P53/SLC7A11 pathway

Abstract: Compelling evidences have revealed the emerging role of ferroptosis in the pathophysiological process of acute lung injury (ALI), but its modulation is not clear. Here, we identified that STAT6 acted as a critical regulator of epithelium ferroptosis during ALI. Firstly, STAT6 expression and activity were increased in the ALI mice models caused by crystalline silica (CS), LPS and X-ray exposure. Followed by confirming the contribution of ferroptosis in the above ALI with ferrostatin-1 and deferoxamine intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…An acetylation defective mutant P53 with 3 mutated lysine residues (K117/161/162R) fails to induce apoptosis and senescence, but still sensitized cells to ferroptosis [35,36]. Yang et al found that STAT6 alleviated acute lung injury by regulating the P53/SLC7A11 pathway to inhibit ferroptosis [37]. Sirt1 has been shown to reduce the acetylation of p53 K382 to prevent cell senescence and atherosclerosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…An acetylation defective mutant P53 with 3 mutated lysine residues (K117/161/162R) fails to induce apoptosis and senescence, but still sensitized cells to ferroptosis [35,36]. Yang et al found that STAT6 alleviated acute lung injury by regulating the P53/SLC7A11 pathway to inhibit ferroptosis [37]. Sirt1 has been shown to reduce the acetylation of p53 K382 to prevent cell senescence and atherosclerosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…p53 has dual and opposite functions in ferroptosis and its function in regulating ferroptosis is apparently cellular context-dependent [26][27][28][29][30][31][32][33]. It has been shown that p53 represses SLC7A11 to induce extrinsic ferroptosis, which releases arachidonate 12-Lipoxygenase, 12S type (ALOX12) from SLC7A11 inhibition [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in addition to the Fas-FasL and granzyme B-perforin pathways, ferroptosis is another CTL-mediated cell death pathway that may also contributes to the CTL effector function in ICI immunotherapy [25]. p53 is a key regulator of ferroptosis and can either promote or suppress ferroptosis by cellular context-dependent mechanisms [26][27][28][29][30][31][32][33]. How p53 is regulated in the ferroptosis pathway is currently incompletely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that ferroptosis inducers (FINs) that inhibit SLC7A11 display significant radiation sensitizing effects on tumor organoids and xenografts derived from patients with p53 deficiency or mutation. Accordingly, activation of p53 and RT-induced ferroptosis leads to better clinical outcomes for RT in cancer patients, and it is suggested that these FINs be used in combination with radiotherapy to treat p53 mutant cancers ( Lei et al, 2021 ; Yang et al, 2022 ).…”
Section: The Role Of Tumor Suppressor Protein P53 In the Regulation O...mentioning
confidence: 99%